POTENSI DAN PELUANG INVESTASI UNGGULAN TAHUN 2021 DI KABUPATEN TAPIN KALIMANTAN SELATAN - Luthfi Hidayat; Ida Rusliyanti (Universitas Kuningan, 2022)
AbstractLeading Investment Potential and Opportunities in 2021, in Tapin Regency, South Kalimantan. The formulation of the research problem is to find out which commodities are superior to invest in. Determination of leading commodities using the AHP (Analytical Hierarchy Process) method. The aim of the research is to produce a study of the Leading Investment Potential. The method used is AHP and Borda. The research results obtained 10 superior commodities from various sectors (18 sectors) in 12 sub-districts in Tapin Regency, the AHP method was combined with the Borda and Bayes methods. There were 10 superior commodities for investment based on input, process, and output considerations collected from 12 sub-districts in Tapin Regency and based on the considerations of the related SKPD. The 10 commodities are: (1) Rice with a score of 0.0399, (2) Corn with a score of 0.0295, (3) Sand excavation with a score of 0.0027, (4) Rubber with a score of 0.0258, (5) Excavation of mountain rocks with a score of 0.0258 0.0247, (6) Tilapia (Fisheries) with a score of 0.0245, (7) Sasirangan cloth (processing industry) with a score of 0.0227, (8) oil palm with a score of 0.0223, (9) fish mas (fishery) with a score of 0.0205, and (10) mixed food stalls (Provision of Accommodation and Provision of Food and Drink) with a score of 0.0202. Kata Kunci: Investment, superior, Tapin Regency, AHP. AbstrakPotensi dan Peluang Investasi Unggulan tahun 2021, di Kabupaten Tapin, Kalimantan Selatan. Rumusan masalah penelitian ini adalah untuk mengetahui komoditas yang unggul untuk berinvestasi. Penentuan komoditas Unggulan dengan menggunakan metode AHP (Analytical Hierarchy Process). Tujuan Penelitian adalah Untuk menghasilkan kajian Potensi Investasi Unggulan. Metode yang digunakan adalah AHP dan Borda. Didapatkan hasil penelitian 10 komoditas unggul dari berbagai sektor (18 sektor) di 12 Kecamatan di Kabupaten Tapin, metode AHP dipadukan dengan Metode Borda dan Bayes. Didapatkan 10 komoditas unggul untuk berinvestasi berdasarkan pertimbangan input, proses, dan output yang dihimpun dari 12 Kecamatan di Kabupaten Tapin dan berdasarkan pertimbandan SKPD terkait. Adapun 10 komoditas tersebut adalah: (1) Padi dengan skor 0.0399, (2) Jagung dengan skor 0.0295, (3) Penggalian pasir dengan skor 0,0027, (4) Karet dengan nilai skor 0.0258, (5) Penggalian batu gunung dengan skor 0,0247, (6) Ikan nila (Perikanan) dengan nilai skor 0,0245, (7) kain sasirangan (industri pengolahan) dengan nilai skor 0,0227, (8) kelapa sawit dengan skor 0,0223, (9) ikan mas (perikanan) dengan nilai skor 0,0205, dan (10) Warung makan campur (Penyediaan Akomodasi dan Penyediaan Makan Minum) dengan skor nilai 0,0202. Kata Kunci: investasi; unggulan; Kabupaten Tapin; AHP.